Calibration of the Advanced LIGO detectors for the discovery of the binary black-hole merger GW150914 - Abbott, B. P.; Abbott, R.; Abbott, T. D.; Abernathy, M. R.; Ackley, K.; Adams, C.; Addesso, P.; Adhikari, R. X.; Adya, V. B.; Affeldt, C.; Aggarwal, N.; Aguiar, O. D.; et al. (American Physical Society (APS), 2017)
In Advanced LIGO, detection and astrophysical source parameter estimation of the binary black hole merger GW150914 requires a calibrated estimate of the gravitational-wave strain sensed by the detectors. Producing an estimate from each detector's differential arm length control loop readout signals requires applying time domain filters, which are designed from a frequency domain model of the detector's gravitational-wave response. The gravitational-wave response model is determined by the detector's opto-mechanical response and the properties of its feedback control system. The measurements used to validate the model and characterize its uncertainty are derived primarily from a dedicated photon radiation pressure actuator, with cross-checks provided by optical and radio frequency references. We describe how the gravitational-wave readout signal is calibrated into equivalent gravitational-wave-induced strain and how the statistical uncertainties and systematic errors are assessed. Detector data collected over 38 calendar days, from September 12 to October 20, 2015, contain the event GW150914 and approximately 16 days of coincident data used to estimate the event false alarm probability. The calibration uncertainty is less than 10% in magnitude and 10° in phase across the relevant frequency band, 20 Hz to 1 kHz.